L'Università allo specchio Questioni e prospettive - Annick Magnier (Studi e saggi, 2016)
This second volume of Quaderni "Cesare Alfieri" offers a consideration on some basic aspects of our academic system. Among the many topics worthy of attention, the Scientific Committee has decided to put the accent on the theme of the relationship between universities and economic and social development. In response to the transformations and the dramatic downsizing of the higher education system, how is it possible to affirm the centrality of the education of the "human capital", aimed at the growth and cohesion of society? The essays gathered in the volume offer, each one from its own point of view, interesting insights and points of discussion on how, at the present time, universities can contribute to the economic and social development of a country in which territorial and social inequalities are deepening, despite reduced public resources, limited degree of autonomy and uncertain relations with other national and local actors.